E-Commerce sebagai Alat Perluasan Pengenalan Produk - M. Khooirul Muttaqin; Nursamsi Nursamsi (Lembaga Pengembangan Kinerja Dosen, 2024)
Someone who already has popularity is an important requirement, or called an Influencer. Website and Search Engine Optimization, utilizing technology does require creativity. Every form of technology needs a trick, because the current market is very plural, especially in the field of E-Commerce Food Quality, the products we produce must have good quality, especially in the culinary field. Taste, shape, texture and color will be an assessment in the eyes of the customer. The more consistent we are in maintaining it, the more it will have an impact on customer loyalty Segmentation in E-Commerce Marketing, companies on their way to expand the market, so it is necessary to segment (market sorting), which goals we will target for product marketing to match the goals that the company wants. Especially in the field of E-Commerce, it will be interesting later when we as business culinary actors are able to donate in E-Commerce.